Basic logic circuits and arithmetic subsystems for low-power applications - Law, Chong Fatt. (2008)
Due to reasons of both portability and reliability of portable and non-portable electronic products, power consumption has become a paramount issue in today's integrated circuit design environment, and is certain to remain so for a long time to come. This thesis reports on several high-performance transistor-level circuit techniques that are useful in both logic circuit and arithmetic subsystem implementations, with their suitability for low-voltage, low-power environments as the central guiding principle. Extensive comparisons between the proposed circuits and other previously reported ones in related fields, through circuit simulations and experimental measurements, whenever possible, have been performed to evaluate their competitiveness.